Approaches to organic sweet potato cultivation: managing nematodes, pests, and soil health with winter cover crops and biopesticides - Schloemer, Claire M.; Graham, Scott H.; Wang, Koon-Hui; Sipes, Brent S.; Lawaju, Bisho R.; Lawrence, Kathy S. (Frontiers in Plant Science, 2025)
The growing demand for organic sweet potato production underscores the need for sustainable pest management and soil health strategies. This study evaluated six winter cover crop systems followed by summer sweet potato, with and without biopesticide applications, to manage Meloidogyne incognita and insect pests while assessing soil health indicators. Marketable yield was the highest after wheat (20,679 kg/ha), exceeding the fallow treatment by >2,000 kg/ha. Biopesticide use further increased yield (+700 kg/ha), reduced insect damage by 36%–40% (p ≤ 0.05), and enhanced crop value by $33/ha. At planting, M. incognita densities were similar across treatments, but by midseason, they were the lowest following rye. Wireworm damage did not vary by cover crop, although biopesticides provided significant protection. Cover crops also shaped nematode communities, with crimson clover, wheat, and mixed systems supporting higher structural index values later in the season, while enrichment index and fungi to bacteria ratios remained unchanged. Soil microbial respiration peaked at planting, especially after wheat and the cover crop mix, and microbial biomass increased across all cover crop treatments, with rye supporting the highest growth. Radish and wheat showed trends toward lower M. incognita populations and greater economic returns, although the effects were not statistically significant. Canonical correspondence analysis revealed nematode communities, microbial abundance, and soil CO2 flux as key drivers of yield. In 2022, yield was negatively associated with M. incognita but positively correlated with fungi to bacteria and Gram-positive to Gram-negative bacteria (GP: GN) ratios; by 2023, yield was instead negatively associated with fungivorous nematodes and microbial respiration and positively associated with protozoa biomass and protozoa to bacteria ratios. Overall, combining cover crops with biopesticides improved yield, reduced pest pressure, and enhanced soil biological function, demonstrating a promising strategy for sustainable organic sweet potato production.